Russian aviators with seaplane 'Land of the Soviets,' Seattle, 1929 - Staff Photographer Seattle Post-Intelligencer
A three-man crew flying the large all-metal, twin-engine plane "Land of the Soviets" made the first flight from Moscow to New York City in 1929. After a ten-day delay in Siberia due to bad weather, they landed at Seward, Alaska, on September 27th, then proceeded to Sitka on September 29th. A week later they arrived in Seattle where their twin floats were replaced by wheels at Sand Point Naval Air Station. Eventually, the Russian crew did make it to New York, where they were greeted by cheering crowds. Handwritten on image: Airplanes - Land of Soviets. Handwritten on sleeve: Airplanes - Russia - Information from American Aviation Historical Society Journal, Fall 1968, p.224-225. Land of the Soviets (Russian flyers visit Seattle). 1 glass negative: b&w; 4 x 5 in.; dichroic fog